2016
DOI: 10.1177/1687814015627978
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion stability and thermophysical properties of environmentally friendly graphite oil–based nanofluids used in machining

Abstract: As environmentally friendly cutting fluids, vegetable-based oil and ester oil are being more and more widely used in metal cutting industry. However, their cooling and lubricating properties are required to be further improved in order to meet more cooling and lubricating challenges in high-efficiency machining. Nanofluids with enhanced heat carrying and lubricating capabilities seem to give a promising solution. In this article, graphite oil-based nanofluids with LB2000 vegetablebased oil and PriEco6000 unsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…The thermal conductivity of ethanol (0.171 W/mK) was found to be the highest among all the fluids at 10 • C [23], while ester oil had the lowest thermal conductivity of 0.161 W/mK at 30 • C. Although an increase in temperature decreased the thermal conductivity, temperature change has the least significant effect on the thermal conductivity of the hybrid lubri-coolants. At 30 • C, the thermal conductivity of ethanol was 0.168 W/mK, that of ethanol-ester oil (1:0.25) was 0.167 W/mK, that of ethanol-ester oil (1:0.5) was 0.165 W/mK, that of ethanol-ester oil (1:1) was 0.162 W/mK, and that of ester oil was 0.158 W/mK [24]. A small reduction in thermal conductivity was observed in this range of temperatures.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The thermal conductivity of ethanol (0.171 W/mK) was found to be the highest among all the fluids at 10 • C [23], while ester oil had the lowest thermal conductivity of 0.161 W/mK at 30 • C. Although an increase in temperature decreased the thermal conductivity, temperature change has the least significant effect on the thermal conductivity of the hybrid lubri-coolants. At 30 • C, the thermal conductivity of ethanol was 0.168 W/mK, that of ethanol-ester oil (1:0.25) was 0.167 W/mK, that of ethanol-ester oil (1:0.5) was 0.165 W/mK, that of ethanol-ester oil (1:1) was 0.162 W/mK, and that of ester oil was 0.158 W/mK [24]. A small reduction in thermal conductivity was observed in this range of temperatures.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The study recommended the use of mineral oil as cutting fluids for machines as this could reduce the amount of waste oil from the manufacturing processes. Su et al [10] studied experimentally and theoretically the effect of different ultrasonication times on the dispersion stability, viscosity and thermal conductivity of LB2000 vegetable-based oil and PriEco6000 unsaturated polyol ester dispersed with graphite particles of 35 nm at different concentrations (0.05, 0.25 and 0.5 vol%). The graphite oil-based nanofluids were prepared using the two-step method.…”
Section: Review Of the Use Of Other Liquids As Base Fluid For Nanocoolantmentioning
confidence: 99%
“…Nevertheless, the rheology of different vegetable oils-based nanolubricant needs to be explored more. The comparative viscosity analysis of LB2000 vegetable oil-based lubricant and PriEco6000 unsaturated polyol ester by adding varying concentrations of graphite nanoparticles was conducted by Su et al (2016). The outcomes showed that the viscosity enhances with the rise of nanoparticle concentration for both oils.…”
Section: Introductionmentioning
confidence: 99%